The Effect of Combination of Benson Relaxation and Natural Sounds on Pain Levels in Postoperative Section Caesarea - Dyah Triwulan; Emiliani Elsi Jerau; Suci Khasanah (Java Nursing Journal, 2026)
Background: Patients who undergo cesarean sections typically experience postoperative pain, which can cause stress, hinder movement, and delay recovery. Pain can be managed through pharmacological and non-pharmacological therapies, one of which is the combination of Benson Relaxation and natural sounds. Purpose: To evaluate the effect of combining Benson relaxation and natural sounds on pain levels in patients after cesarean section at Bunda Arif Purwokerto Mother and Child Hospital. Methods: A single-group pre-test design was used, with 32 participants selected randomly. Pain was measured using a Numerical Rating Scale (NRS) before and after the intervention. Pain was reassessed after a 15-minute intervention. Results: Before the intervention, the majority of participants reported moderate pain (31 participants, 96.9%). After the intervention, the majority reported mild pain (30 participants, 93.8%). The Wilcoxon signed-rank test yielded a p-value of 0.001 (<0.05), suggesting the combination of Benson relaxation and natural sounds significantly reduces pain. Conclusion: This combination technique is effective as a complementary therapy for pain management following cesarean section. Relevance to clinical practice: This simple 15-minute intervention can be integrated into routine post-cesarean nursing care to reduce pain and promote comfort. It is low-cost, non-invasive, and easy to deliver, supporting early mobilization and recovery while potentially reducing reliance on analgesics and related side effects.